Limonoids From the Genus Melia (Meliaceae): Phytochemistry, Synthesis, Bioactivities, Pharmacokinetics, and Toxicology - Fan, Wenxiang; Fan, Linhong; Wang, Zhengtao; Yang, Li (Frontiers in Pharmacology, 2022)
Limonoids, as the vital bioactive chemical compounds in genus Melia plants, have attracted significant attention owing to their exclusive structural characteristics and remarkable biological activity. These compounds can be usually classified into two categories, including the ring-intact group and the ring-C-seco group. Benefiting from the development of separation and analysis technology, more than 200 limonoids have been isolated and identified from this genus. There is growing evidence that limonoids from genus Melia possess diverse pharmacological activities, especially anti-cancer effects, insecticidal activities, and anti-botulism effects. Toosendanin, one of the paramount limonoids, was considered as the pivotal bioactive marker in two medicinal herbs, including Melia toosendan Sieb. et Zucc and Melia azedarach L. In particular, limonoids are found to exhibit non-negligible toxic effects, a finding which needs further research. Besides this, the lack of clinical research data seriously hinders its further development and utilization, and necessary clinical trials should be taken into consideration. In this review, we systematically summarized the phytochemical compounds and their synthesis methods, pharmacological activities, and the structure–activity relationship, pharmacokinetics, and toxicology of genus Melia-derived limonoids. We believe that this up-to-date review could provide scientific evidence for the application of limonoids as agents beneficial to health in future clinical practice.